2015
DOI: 10.1161/hypertensionaha.114.04718
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 and Blood Pressure in Young and Healthy Adults from the General Population

Abstract: All study participants included in the current analysis are participants of the prospective genetic and phenotypic determinants of BP and other cardiovascular risk factors (GAPP) study. Detailed information Abstract-Hypertension and diabetes mellitus are highly correlated, but the underlying mechanisms are only partly understood.Therefore, the aim of our study was to investigate the relationships between plasma levels of glucagon-like peptide-1, a key factor in the regulation of glucose homeostasis, and variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Our meta-analysis showed that SBP was reduced by approximately 5 mmHg, which may be a cardioprotective benefit. A study based on healthy adults found that plasma levels of fasting GLP-1 are significantly and positively related to the blood pressure indices assessed [60]. The increase in GLP-1 levels could be a compensatory response to individual BP elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis showed that SBP was reduced by approximately 5 mmHg, which may be a cardioprotective benefit. A study based on healthy adults found that plasma levels of fasting GLP-1 are significantly and positively related to the blood pressure indices assessed [60]. The increase in GLP-1 levels could be a compensatory response to individual BP elevations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found an effect of GLP‐1 on hyperglycaemia‐induced impairment of endothelium‐dependent relaxation, but as we were not able to show a similar effect of liraglutide, it is uncertain if this is the major mechanism resulting in the lowering of BP in diabetic patients treated with GLP‐1 analogues. Furthermore, it is noteworthy that GLP‐1 plasma levels have been found to be associated with BP in normoglycaemic young healthy adults as well (Krisai et al ., ), demonstrating that there may be other GLP‐1 effects of importance that affect BP.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, the cardiac effects of GLP1 analogs have led to the amelioration of myocardial ischemia and to the restriction of infarct size (9), and GLP1 infusion could improve heart function (10). GLP1 in plasma was associated with blood pressure levels in a human population study (11). Further, GLP1 or its analogs were shown to lower blood pressure in rodents and human subjects (12)(13)(14).…”
Section: Glp1mentioning
confidence: 99%